Thermotolerance of Isolated Mitochondria Associated with Heat Shock Proteins - Chou, Mei (1989)
Mitochondria isolated from 2-day-old etiolated soybean (Glycine max) seedlings which had been subjected to various heat shock treatments, i.e. (A) 28°C (2 h), (B) 38°C (2 h), (C) 38°C (2 h)-42.5°C (0.5 h), and (D) 38°C (2 h)-42.5°C (0.5 h)-28°C (4 h), were monitored for O(2) uptake using an oxygen electrode. Mitochondria isolated after all four heat shock treatments were active in O(2) consumption at 28°C in response to succinate and ADP (derived P/O ratios were 1.6, 1.7, 1.3, and 1.3, respectively.) The mitochondria from all four treatments were also active in O(2) uptake at 42.5°C. However, only mitochondria isolated after treatment (C) were tightly coupling at 42.5°C (derived ADP/O ratio was about 1.4). Combined with our earlier findings on the subcellular localization of heat shock proteins, our present data demonstrate that association of heat shock proteins with mitochondria by treatment (C) enables them to phosphorylate at 42.5°C (i.e. they become thermotolerant). Isolated mitochondria from treatment (C) and treatment (A) were compared by electron microscopy. They appeared to be very similar and no significant ultrastructural differences were noted.